The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/mlr.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional Surrogate Decision Makers for Hospitalized Older Adults

Abstract: This study shows that both traditional and nontraditional surrogates, who are a patient's primary care giver have similar relationships with patients. The findings of this study suggest that requiring family members such as grandchildren to take the extra step of formal appointment through a legal channel may not be necessary to protect patients. Therefore, broader state laws expanding the list of surrogates authorized by state statute to include more nontraditional surrogates may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…During the time of this study, Indiana state default health care consent law, was described as having a narrow construction. 16,17 Therefore, our findings may only be transferable to states with similarly restrictive surrogate laws versus those states that allow broader representation. Although the state law used in this study was considered restrictive, the VA was included in this study and the federal law used at the VA is considered broad and inclusive.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…During the time of this study, Indiana state default health care consent law, was described as having a narrow construction. 16,17 Therefore, our findings may only be transferable to states with similarly restrictive surrogate laws versus those states that allow broader representation. Although the state law used in this study was considered restrictive, the VA was included in this study and the federal law used at the VA is considered broad and inclusive.…”
Section: Discussionmentioning
confidence: 91%
“…Although there is the possibility of sampling bias, the results of this survey are in alignment with prior studies which found a similar low level of knowledge of surrogate health care law. 3,5,16,17 Lastly the residents were asked to recall the education they received during residency about surrogate decision making laws. This response relies on the medical residents' ability to remember incidents of education.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy would be providing assistance for such individuals to identify a non-traditional surrogate decision-maker and encourage them to have end-of-life discussions with the identified person. Reporting a similar rate of patient visitation and end-of-life discussion with the patient between traditional (i.e., immediate family members) and non-traditional surrogates (i.e., relatives and friends) in hospital settings, Comer et al (2018) suggested state-specific, surrogate laws should include more non-traditional surrogates to ensure those without a traditional surrogate also has someone to discuss end-of-life care with and speak for the person at the end of life. This may be particularly important to older Blacks/African-Americans, whose caregivers involve much larger, extended family and friends than Whites (American Psychological Association, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, nearly 10% of patients select nonrelatives as their healthcare agents (56). Clinicians are often unfamiliar with these laws, which vary considerably from state to state (3,(57)(58)(59). Institutions should manage decisionmaking for unrepresented patients using collaboration between the clinical team and a diverse interprofessional, multidisciplinary committee rather than ad hoc by treating clinicians.…”
Section: Recommendationmentioning
confidence: 99%